Beeconomy : what women and bees can teach us about local trade and the global market - Horn, Tammy, 1968- (University Press of Kentucky, 2012)
Queen bee. Worker bees. Busy as a bee. These phrases have shaped perceptions of women for centuries, but how did these stereotypes begin? Who are the women who keep bees and what can we learn from them? Beeconomy examines the fascinating evolution of the relationship between women and bees around the world. From Africa to Australia to Asia, women have participated in the pragmatic aspects of honey hunting and in the more advanced skills associated with beekeeping as hive technology has advanced through the centuries. Synthesizing the various aspects of hive-related products, such as beewax and.